Pharmaceutical cocrystallization: an effective approach to modulate the physicochemical properties of solid-state drugs - Dai, Xia-Lin; Chen, Jia-Mei; Lu, Tong-Bu (CrystEngComm, 2018)
Pharmaceutical cocrystallization affords an opportunity to modify the physicochemical properties of a solid-state drug without covalent modification of its molecular structure. This review presents an update on various applications of pharmaceutical cocrystallization with considerations on both cocrystals and salts, focusing on the property modification relevant to clinical efficacy and safety, and manufacturability of drugs. Some prominent examples of drug cocrystals/salts, which exhibit improved solubility and/or permeability and pharmacokinetics, stability and mechanic properties, are highlighted. This highlight presents an update on applications of cocrystallization to modify properties relevant to efficacy, safety, and manufacturability of drugs.